A novel small nucleolar RNA (U16) is encoded inside a ribosomal protein intron and originates by processing of the pre-mRNA. - Fragapane, P (1993)
We report that the third intron of the L1 ribosomal protein gene of Xenopus laevis encodes a previously uncharacterized small nucleolar RNA that we called U16. This snRNA is not independently transcribed; instead it originates by processing of the pre-mRNA in which it is contained. Its sequence, localization and biosynthesis are phylogenetically conserved: in the corresponding intron of the human L1 ribosomal protein gene a highly homologous region is found which can be released from the pre-mRNA by a mechanism similar to that described for the amphibian U16 RNA. The presence of a snoRNA inside an intron of the L1 ribosomal protein gene and the phylogenetic conservation of this gene arrangement suggest an important regulatory/functional link between these two components.